PhD on Track: Open Science as a new track - Faber, Hege Charlotte; Kavli, Fredrik Andersen; Grote, Michael; Låg, Torstein (Septentrio Conference Series, 2018)
PhD on Track is a web resource aimed primarily at PhD candidates and early career researchers. The ambition is to provide an accessible point of departure for beginning researchers related to searching and reviewing scholarly literature, and to sharing and publishing reports and data. It can be challenging for new candidates (or even for experienced researchers) to find their way in the tangle of new guidelines and practices on openness, data management, publishing, and adjoining issues. PhD on Track is intended to help, by collecting and organising in one resource, providing an overview of the most essential information. In our poster, we wish to focus on recent major revisions to the resource, and in particular on the new module Open Science. Revisions were made in response to important developments regarding new national and international guidelines on open publishing and data management, and in open science in general. PhD on Track, and the new Open Science module in particular, collects and organises relevant information – and discusses some of the fundamental issues on open access publishing, open archives, research data, and data management, including how to make data management plans and how to handle sensitive data. There are also sections on pre-registration, research ethics, copyright issues, and research assessment. PhD on Track is an open, freely available resource that was originally launched in 2013, as a co-operation between Norwegian and Danish institutions. From 2017, it is operated by 6 Norwegian institutions: the four university libraries in Bergen, Oslo, Trondheim, and Tromsø, in addition to the libraries at NHH Norwegian School of Economics Library and Western Norway University of Applied Sciences. While PhD on Track provides more detail on Norwegian policies and guidelines, it has been designed with an international audience in mind. It will be relaunched in the autumn of 2018.